Seaweed Hypnea sp. culture in Coxs Bazar coast, Bangladesh (Bangladesh Journal of Zoology, 2017)
The culture of a red seaweed Hypnea sp. in three locations of Coxs Bazar coast, Saint Martin Island, Inani and Bakkhali with net method of 4 × 4 m coir rope net was evaluated. Seaweed was partially harvested at 15 days interval during December 2015 to January 2016. Daily growth rate of cultured Hypnea sp. was significantly higher (3.21 ± 0.01% day-1) in Saint Martin while Inani had the lowest (0.41 ± 0.06% day-1). Biomass yield of Hypnea sp. (3.81 ± 0.04 kg fresh wt.m?2) gained highest in Saint Martin than in Bakkhali (3.34 ± 0.10) and Inani (2.70 ± 0.02). Growth rate of seaweeds had a significant correlation with NO3-N (p < 0.05) but not with PO4-P. Culture of seaweed along those sites added a new dimension of prospect and possibility of seaweed mariculture in Bangladesh coast.Bangladesh J. Zool. 45(1): 37-46, 2017